Functional and Genomic Features of a Lytic Salmonella Phage vB_StyS_KFSST1 for Development as New Feed Additive - Kim, Su-Hyeon; Choi, In Young; Cho, Gyu-Sung; Franz, Charles M.A.P.; Park, Mi-Kyung (Food science of animal resources, 2025)
Lytic phages have emerged as promising candidates for feed additives for controlling Salmonella in poultry, owing to their high specificity, self-replication, and excellent stability. According to the European Food Safety Authority (EFSA) guidelines, their application as feed additives requires evaluation of safety, host range, in vitro and in vivo efficacy, and stability. Thus, this study aimed to evaluate the functional and genomic features of vB_StyS_KFSST1, previously isolated from poultry processing wastewater, as a candidate for the development of a new feed additive against Salmonella. The phage exhibited dual serotype-specific lytic activity against S. Enteritidis and S. Typhimurium, with high plating efficiency. Infection kinetic analysis revealed its rapid adsorption and a sustained inhibitory effect lasting up to 12 h for both serovars. Whole genome sequencing of the phage was performed using the Oxford Nanopore PromethION 2 Solo platform. The phage genome consisted of 47,149 bp dsDNA, containing 98 open reading frames and two tRNA genes. No lysogeny-related, antibiotic resistance, or virulenceassociated genes were found in its genome, whereas phage-susceptible Salmonella strains carried multiple antibiotic resistance and virulence genes. Phylogenetic and taxonomic analyses finally clustered the phage with other lytic Salmonella phages, classifying it within the genus Skatevirus. These findings highlight the potential of lytic phage vB_StyS_KFSST1 as a promising candidate for the development of a feed additive to control Salmonella in poultry husbandry. KCI Citation Count: 0